Răspuns :
[tex]1)\frac{ 35 }{ 11 } - \frac{ 14 }{ 11 } = [/tex]
[tex]\frac{35-14}{11} = [/tex]
[tex]\frac{21}{11} [/tex]
[tex]2)\frac{ 35 }{ 24 } - \frac{ 17 }{ 24 } = [/tex]
[tex]\frac{35-17}{24} = [/tex]
[tex]\frac{18}{24} = [/tex]
[tex]\frac{3}{4} [/tex]
[tex]3)\frac{ 29 }{ 12 } - \frac{ 44 }{ 48 } = [/tex]
[tex]\frac{29}{12}-\frac{11}{12} = [/tex]
[tex]\frac{29-11}{12} = [/tex]
[tex]\frac{18}{12} = [/tex]
[tex]\frac{3}{2} [/tex]
[tex]1)1 \frac { 5 } { 18 } - \frac{ 4 }{ 9 } = [/tex]
[tex]\frac{18+5}{18}-\frac{4}{9} = [/tex]
[tex]\frac{23}{18}-\frac{4}{9} = [/tex]
[tex]\frac{23}{18}-\frac{8}{18} = [/tex]
[tex]\frac{23-8}{18} = [/tex]
[tex]\frac{15}{18} = [/tex]
[tex]\frac{5}{6} [/tex]
[tex]2)3 \frac { 5 } { 6 } - \frac{ 7 }{ 8 } = [/tex]
[tex]\frac{18+5}{6}-\frac{7}{8} = [/tex]
[tex]\frac{23}{6}-\frac{7}{8} = [/tex]
[tex]\frac{92}{24}-\frac{21}{24} = [/tex]
[tex]\frac{92-21}{24} = [/tex]
[tex]\frac{71}{24} [/tex]
[tex]3)2 \frac { 9 } { 10 } - 1 \frac { 3 } { 8 } = [/tex]
[tex]\frac{20+9}{10}-\frac{1\times 8+3}{8} = [/tex]
[tex]\frac{29}{10}-\frac{1\times 8+3}{8} = [/tex]
[tex]\frac{29}{10}-\frac{8+3}{8} = [/tex]
[tex]\frac{29}{10}-\frac{11}{8} = [/tex]
[tex]\frac{116}{40}-\frac{55}{40} = [/tex]
[tex]\frac{116-55}{40} = [/tex]
[tex]\frac{61}{40} [/tex]
Sper ca ti-am fost de folos. Succes!!!